Inductive Risk and Regulatory Toxicology: A Comment on de Melo-Martín and Intemann. - Hicks, Daniel J. (Philosophy of Science, 2018)
Inmaculada de Melo-Martín and Kristen Intemann consider whether, from the perspective of the argument from inductive risk, ethical and political values might be logically, epistemically, pragmatically, or ethically necessary in the "core" of scientific reasoning. In each case, they argue that there are significant conceptual problems. In this comment, employing regulatory uses of high-throughput toxicology at the US Environmental Protection Agency as a case study, I respond to some of their claims about the notion of "pragmatic necessity." I conclude that, while an inductive risk framework has some significant limitations, it is still conceptually and rhetorically valuable.